Keynote: What is the State of E-Learning? Reflections on 30 Ways Learning is Changing - Curtis J. Bonk (Flexible Learning Association of New Zealand, 2016)
This paper is based on a keynote talk delivered at the biannual DEANZ Conference, at the University of Waikato in Hamilton, New Zealand in April 2016. As highlighted in that talk, we have entered Education 3.0; an age filled vast resource abundance and extensive opportunities for learner empowerment. During the past decade, there have emerged at least 30 different ways in which learning in changing; for instance, it is becoming increasingly collaborative, global, mobile, modifiable, open, online, blended, massive, visually-based, hands-on, ubiquitous, instantaneous, and personal. These 30 learning and technology-related changes reflect three distinct "mega-trends;" namely, (1) learner engagement, (2) the pervasive access to learning, and (3) the customisation and personalization of learning.